Potensi dan Daya Saing Ekspor Sarang Burung Walet Indonesia di Pasar China - Maharani, Rizka Widya; Wijaya, Riko Setya; Marseto, Marseto (Jurnal Ilmiah Wahana Pendidikan, 2024)
International trade in export and import activities can benefit each countries and can be a form collaborations and communication between countries. One of the export commodities in the Indonesian livestock sector is swift's nest. With production reaching 79.55% of world SBW production, making Indonesia the world's largest SBW producer. Chinese people use SBW as the main ingredient for luxury food and the development of herbal medicines in China. So it can be said that commodities from Indonesia have the opportunity to be included in the list of export commodities to the Chinese market. However, in perfecting export market mapping, it is important for exporters to see market potential or market segmentation and commodity competitiveness in the Chinese market. This research uses a descriptive method qualitative approach to find out whether the swift's nest commodity can be exported to China, whether this commodity has potential and have competitiveness in the Chinese market. The result of this study, through the results of data analysis on the tradepmap regarding countries supplying swift's nest to the Chinese market, it can be concluded that Indonesia is able to market its swallow's nest commodities in the Chinese market. Indonesia is able to compete with Malaysia, which is also the largest exporter of swift's nest in the world. With the productivity of swift's nest in Indonesia continuing to increase every year.